2019
DOI: 10.1371/journal.pntd.0007645
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study to understand how Ebola Virus Disease affected nutrition in Sierra Leone—A food value-chain framework for improving future response strategies

Abstract: BackgroundThis study sought understand how the 2014–2016 EVD Virus Disease (EVD) outbreak impacted the nutrition sector in Sierra Leone and use findings for improving nutrition responses during future outbreaks of this magnitude.MethodologyThis qualitative study was iterative and emergent. In-depth interviews (n = 42) were conducted over two phases by purposively sampling both key informants (n = 21; government stakeholders, management staff from United Nations (UN) agencies and non-governmental organizations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
107
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(108 citation statements)
references
References 36 publications
0
107
0
Order By: Relevance
“…Eleven articles from various geographical and disease contexts highlighted the psychological implications of mass quarantine as emotional distress and symptoms of mental illness. [22][23][24][25][27][28][29][30][31][32]35 Among people in or after quarantine, some experienced emotional distress, including:…”
Section: Psychological Distressmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven articles from various geographical and disease contexts highlighted the psychological implications of mass quarantine as emotional distress and symptoms of mental illness. [22][23][24][25][27][28][29][30][31][32]35 Among people in or after quarantine, some experienced emotional distress, including:…”
Section: Psychological Distressmentioning
confidence: 99%
“…annoyance, 32 anxiety, 25,29 boredom, 23,25,32 disappointment and life dissatisfaction, 24,32,35 fear of infection, 23,25,30,34 isolation, 23,25,32 . 27 Nevertheless, this result was prone to reporting bias as the survey response rate was less than one per cent; 27 confirmation of psychiatric disorders required further clinical diagnosis, on which data were not available.…”
Section: Psychological Distressmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, many studies have been conducted to evaluate the impact of epidemics and natural disasters on food security. Most studies posited that many households are most likely to be hit due to negative impact of epidemics on crop production, incomes, movements and food chains which increases the problem of food and nutritional insecurity throughout the world (Kodish et al, 2019;Agrilinks, 2020). For instance, the 2013-2016 Ebola outbreaks in West Africa negatively disrupted the food system and markets, primarily in Sierra Leone, Guinea, and Liberia (Gatiso et al, 2018;FAO, 2015a).…”
Section: Impact Of Covid-19 On Food Securitymentioning
confidence: 99%
“…In a qualitative exploration of flu behavior during the 2009 H1N1 flu outbreak, Flowers and colleagues (2016) found that the majority of work surrounding hygiene, personal protection, and caregiving during the outbreak collided with gender inequities and unfairly burdened women, worsening gender-based inequities and women's vulnerabilities. Via focus groups, interviews, and observations with communities after the EVD outbreak in Sierra Leone, qualitative researchers found that quarantine put people in danger of starvation given preexisting food insecurities (Kodish et al, 2019). Similarly, during EVD, bushmeat bans contradicted people's experiences of safely consuming wild meat, and the criminalization of bushmeat worsened distrust between communities and outbreak workers (Bonwitt et al, 2018).…”
mentioning
confidence: 99%